The comparison of frictional resistance in titanium, self-ligating stainless steel, and stainless steel brackets using stainless steel and TMA archwires: An in vitro study - Syed Altaf Khalid; Vadivel Kumar; Prithviraj Jayaram (Wolters Kluwer Medknow Publications, 2012)
Aim: The aim of the study was to compare the frictional resistance of titanium, self-ligating stainless steel, and conventional stainless steel brackets, using stainless steel and titanium molybdenum alloy (TMA) archwires. Materials and Methods: We compared the frictional resistance in 0.018 slot and 0.022 slot of the three brackets - titanium, self-ligating stainless steel, and conventional stainless steel - using stainless steel archwires and TMA archwires. An in vitro study of simulated canine retraction was undertaken to evaluate the difference in frictional resistance between titanium, self-ligating stainless steel, and stainless steel brackets, using stainless steel and TMA archwires. Results and Conclusion: We compared the frictional resistance of titanium, self-ligating stainless steel, and conventional stainless steel brackets, using stainless steel and TMA archwires, with the help of Instron Universal Testing Machine. One-way analysis of variance (ANOVA), Student's "t" test, and post hoc multiple range test at level of <0.05 showed statistically significant difference in the mean values of all groups. Results demonstrated that the titanium, self-ligating stainless steel, and stainless steel brackets of 0.018-inch and 0.022-inch slot had no significant variations in frictional résistance. The self-ligating bracket with TMA archwires showed relatively less frictional resistance compared with the other groups. The titanium bracket with TMA archwires showed relatively less frictional resistance compared with the stainless steel brackets.